(untitled) (Global Journal of Human-Social Science, 2024)
This article contends that addressing environmental concerns in the South African context requires acknowledgment of the intertwined issues of land grabbing, littering, illegal dumping, and inadequate service delivery. It suggests that Pentecostals, as members of diverse communities, should shift their focus from spiritual matters to initiatives aimed at caring for the earth. Therefore, the article delves into Mogale City and Rand West City Local Municipality in South Africa as a case study, illustrating their contribution to the ongoing environmental degradation. The increasing incidence of land grabbing in these areas poses a threat to the pollution of the Wonderfontein spruit/stream, which flows from Kagiso through the townships of Swanieville 1, extensions 2 and 3, and continues east of Mohlakeng township to the west of Bekkersdal township. Inadequate service delivery has resulted in a backlog of waste removal, leading to concerning levels of littering and illegal dumping in both municipalities.